Relative Influence of Socio-Personal Characteristics and Utilization of Fertilizer Technology in Wheat Cultivation - Singh, S.P.; Singh, Jogender; Tyagi, P.K.; Kumar, Rupendra (Indian Journal of Extension Education, 2010)
A study was conducted in Aligarh district of Uttar Pradesh. The study covered ten villages and 300 respondents belong to small categories. The study aim to generalize socio- economic profile of the farmers and utilization of fertilizer technology in the area under study. The study highlighted that majority (63.33%) of the small farmers were in 31 to 45 year age group and living in pucca house. The majority (87.15%) respondents were educated up to high school there annual income range from 10,000 to 25,000 and member of atleast one organization they living in nuclear family system. Only 45.33 per cent respondent adopted the fertilizer technology in the range of 76-100 per cent level of adoption. In the selected area maximum overall adopters were belong to medium adoption categories with their nitrogenous, phosphatic and potassic fertilizers adoption i. e. 44.67, 41.00 and 04.67 per cent respectively. The correlation study indicated that adoption levels of nitrogenous and phosphatic fertilizer were significantly correlated with income and socio economic condition of the respondents.